THE FORM AND FUNCTION OF HYPERBOLIC EXPRESSION IN ONLINE PERFUME ADVERTISMENTS - Voltadewi, Saomi Wahyu (LANTERN (Journal on English Language, Culture and Literature), 2014)
Language in advertising has so many variations. One of them is hyperbolic style. Hyperbole is frequently used in beauty products, for example in perfume. From this case the writer is interested in the hyperbolic expression which occurs in perfume advertisement and she wants to do research which is concerned with the topic. There are two main research questions regarding hyperbolic expression in online perfume advertisement, which are what kind of hyperbolic forms that occur in online perfume advertisement and why the advertiser uses hyperbolic utterances in perfume advertisement. The data are language expressions in the form of words, phrases, and sentences in perfume advertisement. The writer used two main methods in analyzing data. The methods are identity and distributional method. The result of this study shows that perfume advertisements use hyperbolic style in delivering their message. The most common hyperbolic form in online perfume advertisements is single word form. The purpose of using hyperbolic style is to make the advertisement more attractive, therefore the customers will have high interest in buying the products.